1993
DOI: 10.1002/cne.903380104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unilateral partial cochlear lesions in adult cats on the representation of lesioned and unlesioned cochleas in primary auditory cortex

Abstract: We examined the effect of unilateral restricted cochlear lesions in adult cats on the topographic representations ("maps") of the lesioned and unlesioned cochleas in the primary auditory cortex (AI) contralateral to the lesioned cochlea. Frequency (tonotopic) maps were derived by conventional multineuron mapping procedures in anesthetized animals. In confirmation of a study in adult guinea pigs (Robertson and Irvine [1989] J. Comp. Neurol. 282:456-471), we found that 2-11 months after the unilateral cochlear l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
275
2
13

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 333 publications
(314 citation statements)
references
References 92 publications
24
275
2
13
Order By: Relevance
“…The authors suggested that the CF of neurons corresponding to the notch had shifted toward the edge frequencies of the notch so that fewer neurons could respond to the probe tone. These proposed central changes in tonotopic organization induced by a NN are supposed to be similar to those following cochlear damage (Rajan et al 1993). The results of Pantev et al (1999) then corroborate the assumption that long-lasting presentation of a NN induces a ''functional deafferentation.…”
Section: Introductionmentioning
confidence: 79%
“…The authors suggested that the CF of neurons corresponding to the notch had shifted toward the edge frequencies of the notch so that fewer neurons could respond to the probe tone. These proposed central changes in tonotopic organization induced by a NN are supposed to be similar to those following cochlear damage (Rajan et al 1993). The results of Pantev et al (1999) then corroborate the assumption that long-lasting presentation of a NN induces a ''functional deafferentation.…”
Section: Introductionmentioning
confidence: 79%
“…A maladaptive response to this loss of input causes expansion of the tonotopic map so that this affected portion now becomes responsive to the adjacent frequency at which hearing threshold is normal -the lesion-edge frequency ( Figure 7). Of relevance for human neuroimaging studies, animal research has shown that a restricted cochlear lesion in adult animals drives neuroplastic changes in the frequency gradient within primary auditory cortex (Robertson and Irvine, 1989;Kaas, 1991, Rajan et al, 1993Schwaber et al 1993;Irvine et al, 2001). One theory of TI proposes that it is a consequence of such cortical reorganisation (e.g., Salvi et al, 2000a).…”
Section: Iii) Reorganisation Of the Cortical Tonotopic Mapmentioning
confidence: 99%
“…Although the specific role of hearing loss is debated (see Weisz et al 2006), most cases of tinnitus are accompanied by hearing impairment associated with noise exposure or the aging process. One consequence of hearing loss identified by studies of animals exposed to noise trauma is a reorganization of the tonotopic map in primary auditory cortex (A1), such that sound frequencies near the edge of the cortical region of normal hearing come to be over-represented at the expense of sound frequencies in the region affected by hearing impairment (Robertson and Irvine 1989;Harrison et al 1991;Rajan et al 1993;Eggermont and Komiya 2000). It has been proposed that this overrepresentation of edge frequencies corresponds to the tinnitus sensation (see Rauschecker 1999, for a review).…”
Section: Introductionmentioning
confidence: 99%